Integration of High Order Thinking Skills in Research Method Subject in University - Syamsul Arif; Basyaruddin; Achmad Yuhdi (Britain International for Academic Research (BIAR) Publisher, 2020)
High Order Thinking Skills is the ability to connect, manipulate, and change the knowledge and experience that is owned critically and creatively in determining decisions to solve problems in new situations. In the 21st century or the Industrial Revolution 4.0 era, the learning model continues to change as a form of adjustment to the demands of the development of science and technology. The learning model that used to be still conservative in the auspices of LOTS (Low Order Thinking Skill) with the teacher / lecturer as the center of learning switched to the HOTS (High Order Thinking Skill) model by relying on reasoning, innovation and creativity to solve problems. So, the students become the center of learning. This study aims to design the shape of the HOTS learning model in the Research Methods subject. The prototype of the learning model is developed to be five steps / stages of learning, namely: (1) identifying problems based on observations of learning activities in schools, (2) selecting problems to study, (3) gathering information about the problems to be studied, (4) developing proposals, (5)presentation of proposals. The results of the study showed that the learning process of the Research Methods subject by applying the HOTS-based learning model would lead the students to form a critical attitude, increase independence and gain a lot of experience that are useful to compile scientific works including the completion of thesis preparation.